2010
DOI: 10.1590/s0104-42302010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de consultas médicas e fatores associados: um estudo de base populacional no sul do Brasil

Abstract: Objective. To describe the prevalence of medical visits and associated factors in an adult population of a medium-sized municipality in Southern Brazil. MethOds. A cross-sectional population-based study was carried out in a representative random cluster sampling in Lages, state of Santa Catarina, Brazil. The reference population comprised adults (aged 20 to 59 years) and 2,022 individual were interviewed. The outcome was medical visits during the 12 months prior to the study. Data related to the type of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
4
13
0
7
Order By: Relevance
“…Both in the Northeastern and in the Southeastern region, it was possible to observe a higher prevalence of medical visits among women, older people, richer people, those with more chronic conditions, with negative health self-perception and with a health insurance plan that gives access to medical visits, thus corroborating the findings of other studies 3,4,[14][15][16][17][18][19] . Still, the inequality among men and poorer women decreased when compared to richer people in both assessed macro-regions.…”
Section: Discussionsupporting
confidence: 86%
“…Both in the Northeastern and in the Southeastern region, it was possible to observe a higher prevalence of medical visits among women, older people, richer people, those with more chronic conditions, with negative health self-perception and with a health insurance plan that gives access to medical visits, thus corroborating the findings of other studies 3,4,[14][15][16][17][18][19] . Still, the inequality among men and poorer women decreased when compared to richer people in both assessed macro-regions.…”
Section: Discussionsupporting
confidence: 86%
“…It is also considered that the people with health problems and who negatively assess their health condition tend to visit doctors more often for treatment and follow-up 34 . In the study by Boing et al 35 , the prevalence of medical appointments within the last year was 13% higher among people who self-reported DM and 11% higher among those who classified their health negatively.…”
Section: Discussionmentioning
confidence: 90%
“…Another study, also conducted in southern Brazil and with a population aged 20 to 69 years old, revealed that 45.1% of men attended medical consultations through the SUS in the last month before the interview 13 . There was prevalence of 52.5% of use of the public sector among the adult population aged 20 to 59 years old (both sexes) in a medium-sized municipality in southern Brazil 14 . This study found that adult men without health plan were about 20 times more likely to use public health services than men with health plan.…”
Section: Discussionmentioning
confidence: 96%
“…Medical care is important for both the users of services and the public health system, and for this reason it has been the object of recent studies on the use of health services 12,14 . As noted in this study, in general terms (Table 2), the doctor is the professional with which the men reported having more frequent contact.…”
Section: Discussionmentioning
confidence: 99%